The Pivotal Role of Chemistry in Disease Diagnosis: Advancements in Diagnostic Techniques and Their Medical Implications - Nada Nafea Mageed Mohamed; Shuhad Thaer Yasir Abdulkareem; Bozhin Rahim Muhamad; Abeer Hussein Kamel Saheb (American Journal of Biomedicine and Pharmacy, 2025)
The integration of chemistry in the development and improvement of the techniques used for the diagnosis of diseases is presented. By analyzing in particular the analytical techniques used in the clinical laboratory (among them biochemistry, hematology and immunochemistry), the crucial role of this discipline in medicine has been confirmed, particularly thanks to its implications in the discovery and systematic use of more and more powerful diagnostic techniques (multi-parametric analysis, clinical signals analysis) which illuminates the possibility of a fuller exploitation of the diagnostic potential of the clinical laboratory, with evident advantages in terms of patients and public health. A comprehensive framework describes the main steps leading to the formulation of a chemically based diagnostic product from the definition of the disease and the associated diagnostic needs to the design of the manufacturing process, through the preliminary choice of the chemical formulation. In particular, a review of the analytical methods used to control physical and chemical characteristics of the particulate component and, in some cases, the quality of the dispersions is provided. The methods and the main results of a test case concerning the development of a commercial diagnostic test based on particle enhanced agglutination of latex particles are reported. In the absence of rigorous scientific proof, patients can still be diagnosed based on clinical evidence. However, current pressure from pharmaceutical companies and the legal system have encouraged greater use of scientific methods in diagnostic medicine. Scientists believe this trend has had both positive and negative effects and consider the relative merits and demerits of evidence-based medicine. The most difficult aspect of diagnostic medical testing is developing a conclusive diagnostic test for a given disease. Often, however, the development of research in molecular and genetic biology serves as either lead to diagnostic tests or improved the sensitivity of existing tests. The development of drugs and medical treatments thus may follow advances in the understanding of a disease, which are in turn often based on the foundations of diagnostic tests. On a day-to-day basis in the hospital setting, there is much need for disease tests that are inexpensive and give rapid conclusions. Even after a doctor identifies the group of diseases our body is subjected to, it is often still a long process to conclusively isolate the specific malaise. It is beneficial for patients to have the possibility to rapidly and inexpensively be appraised of their health state.With so much importance riding on a correct diagnosis, it is understandable that diagnostic testing requests for inpatients are textbook problems for medical students, and actual doctors too. However, often the tests themselves are quite exotic so it is useful first to go over some of the most common practical tests available.